Association of Peripheral Blood RASSF1A and CDKN2A Methylation Status with Smoking Behaviour in Nasopharyngeal Carcinoma - Erika Diana Risanti; Aditya Kurniawan; Laila Wahyuningsih; Ery Kus Dwianingsih; Hanggoro Tri Rinonce; Jajah Fachiroh (The Indonesian Biomedical Journal, 2018)
BACKGROUND: Hypermethylation of RASSF1A and CDKN2A is one of epigenetic factor underlies nasopharyngeal carcinoma (NPC) development. Smoking behavior as an NPC’s risk factor causes aberrant DNA methylation. RASSF1A and CDKN2A promoter hypermethylation from peripheral blood cells correlates with smoking behavior. The use of body fluids including peripheral blood as a specimen for DNA methylation analyzes are widely developed, as less invasive method compared to the use of tissue biopsy. This study aims to observe the association between RASSF1A and CDKN2A methylation in peripheral blood and smoking behavioramong NPC patients.METHODS: Newly diagnosed NPC subjects were recruited from ear-nose-throat (ENT) outpatient clinic of Dr. Sardjito Hospital, Yogyakarta. DNA from buffycoat of 19 smokers and 20 non-smokers NPC’s patients were isolated. Bisulphite modification was applied to 500 ng of the isolated DNA. The methylation status was detected by MSP (methylation-specific polymerase chain reaction (PCR)). The association between smoking status and promoter hypermethylation was analysis using Chi-Square test.RESULTS: MSP analysis of RASSF1A showed that 68.42% smoker and 75% non-smoker NPC’s patients were methylated. MSP analysis of CDKN2A showed that 21.05% smoker and 25% non-smoker NPC’s patients were methylated. There was no association between smoking behavior with RASSF1A and CDKN2A methylation (p>0.05).CONCLUSION: Statistical analysis showed that smoking behavior is not associated with methylation of RASSF1A and CDKN2A among NPC’s patients.KEYWORDS: DNA methylation, CDKN2A, RASSF1A, Nasopharyngeal carcinoma, Smoking